Regimes of Risk - Hatcher, Pascale. author. aut Link
XIV, 193 p.
Keywords: With Asia as its backdrop, this book investigates the role played by the World Bank Group (WBG) in conceptualising and promoting new mining regimes tailored for resource-rich country clients. It details a particular politics of mining in the Global South characterised by the transplanting, hijacking and contesting of the WBG's mining agenda.